Satu data Indonesia (one Indonesian data) to actualize public information disclosure and efficacious process management in the Mojokerto city government - Suryahadi, Muhammad Fauzan (Departement Of Accounting, Indonesian Cooperative Institute, Indonesia, 2023)
The rapid advancement of information technology has an impact on governance management, including local government. As the recipient of public services, society desires information disclosure as a measure of local government performance. In response, the President of the Republic of Indonesia established the Satu Data Indonesia (SDI) program. This program creates a database containing all government-related data to streamline the current work system. The SDI database can be used as a resource in local government policymaking. As a result, by providing credible, accountable, and up-to-date data, this program is expected to respond to societal needs. Furthermore, information in the form of public data is hoped to be obtainable in a single location by anyone, at any time, and from any site. This study aims to discover how the One Data Indonesia (SDI) program helps the city government of Mojokerto share information with the public and manage processes well. The literature review method was used in this study. The result of this study shows that SDI implementation still faces numerous challenges. Each component of SDI implementation (data planning, data collection, data checking, and data distribution) has some issues.